A machine for playing in: Exploring the videogame as a medium for architectural design. (January 2020) - Pearson, Luke Caspar
Abstract : This paper aims to investigate what is unique about videogame spaces and their construction, and how they might be utilised by architects. This design-led study establishes videogames as an architectural medium through practice-based research projects, examining game worlds as architectural spaces by developing design methods to analyze their environments. It then discusses developing games as architectural representations combining virtual space with computational rules. The paper's final study suggests how game structures might be applied in design approaches for ostensibly real sites. Through four case study projects, I outline a new form of architectural design practice operating between physical and virtual, reflecting the cultural influence of game worlds and exploring videogame environments as new ways to 'realise' architecture. Highlights: In videogame worlds player interactivity is integral to their architectural design. Architecture designed within game spaces can impart meaning through interaction. Videogame worlds can be sited within the history of architectural representation. Analyzing videogames through architectural design methods expands existing games studies scholarship. New forms of architectural practice will operate across the virtual and physical.